2011
DOI: 10.1073/pnas.1101458108
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in climate assessment for the case of aviation NO

Abstract: Nitrogen oxides emitted from aircraft engines alter the chemistry of the atmosphere, perturbing the greenhouse gases methane (CH 4 ) and ozone (O 3 ). We quantify uncertainties in radiative forcing (RF) due to short-lived increases in O 3 , long-lived decreases in CH 4 and O 3 , and their net effect, using the ensemble of published models and a factor decomposition of each forcing. The decomposition captures major features of the ensemble, and also shows which processes drive the total uncertainty in several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
128
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(152 citation statements)
references
References 39 publications
23
128
0
1
Order By: Relevance
“…5, top), there is clearly a large uncertainty in the magnitude of impact from AIR in the middle of this century. Although there is a considerable spread between the models (see Holmes et al (2011) for a discussion of RF uncertainties when modelling aviation NO x ), the uncertainty is mostly induced by the large spread of emissions between the various scenarios , whereas the ensemble mean O 3 RF is 61 (± 14) mW m −2 for the A1B scenario and only 19 (± 6.8) mW m −2 for B1 ACARE in 2050, just slightly higher than in 2000 (18 ± 3.6 mW m −2 ). However, it should be noted here that B1 ACARE is a mitigation scenario assuming extensive technological improvements to the aircraft and is considered very optimistic in terms of emissions (see H2011).…”
Section: Synthesis Of Rf In Various Scenariosmentioning
confidence: 99%
“…5, top), there is clearly a large uncertainty in the magnitude of impact from AIR in the middle of this century. Although there is a considerable spread between the models (see Holmes et al (2011) for a discussion of RF uncertainties when modelling aviation NO x ), the uncertainty is mostly induced by the large spread of emissions between the various scenarios , whereas the ensemble mean O 3 RF is 61 (± 14) mW m −2 for the A1B scenario and only 19 (± 6.8) mW m −2 for B1 ACARE in 2050, just slightly higher than in 2000 (18 ± 3.6 mW m −2 ). However, it should be noted here that B1 ACARE is a mitigation scenario assuming extensive technological improvements to the aircraft and is considered very optimistic in terms of emissions (see H2011).…”
Section: Synthesis Of Rf In Various Scenariosmentioning
confidence: 99%
“…Wild et al (2012) examined the impact of solar-flux variations, while and Berntsen et al (2005) investigated the effects of atmospheric mixing. However, as reported in Holmes et al (2011), modelbased estimates of aviation NO x -induced changes in O 3 vary by up to 100 %, largely because of differences between models in the ratios of NO : NO 2 and OH : HO 2 , background NO x levels, location and time of emissions, the amount of sunlight, and in atmospheric mixing (Holmes et al, 2011). Recent studies by Olsen et al (2013) and Brasseur et al (2014) found considerable differences between a set of climatechemistry models (CCMs) and chemistry transport models (CTMs) in comparisons of the background atmosphere and aviation NO x -induced changes in ozone.…”
Section: Introductionmentioning
confidence: 72%
“…The long-term reduction is associated with negative forcing (Wild et al, 2001;Stevenson et al, 2004). The short-term O 3 forcing is one of the major contributors to the overall aviation forcing and dominates the net O 3 forcing (Lee et al, 2009;Holmes et al, 2011). Since our simulations were performed with fixed CH 4 mixing ratios at the boundary layer, the calculated changes in O 3 concentration are the short-term changes.…”
Section: Ozonementioning
confidence: 99%
“…Both O 3 and CH 4 are greenhouse gases. Hence, the net RF from aviation NO x depends on which pathway dominates, and this depends on emission scenarios, background concentrations and the chemical rate coefficients [17]. Depending on the location of the emission, the net RF of these emissions could be positive or negative [10].…”
Section: Climate Impact From Aviationmentioning
confidence: 99%